2011
DOI: 10.2341/10-356-l
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Surface Roughness and Microhardness of Restorative Materials Submitted to Erosive Challenges

Abstract: The aim of this study was to evaluate the effect of different acidic solutions on the microhardness and surface roughness of restorative materials. The 120 specimens of restorative materials (Fuji II LC, Vitremer, Supreme XT, and Supreme XT + Biscover LV) were randomly divided into three groups according to the immersion media: hydrochloric acid, soft drink, or distilled water. Over a period of five weeks, the groups were immersed in the solutions, which were changed weekly. Data were tested using analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
18

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 21 publications
2
45
0
18
Order By: Relevance
“…1 This study employed chemical challenges with acidic solutions, such as hydrochloric acid to simulate the gastric reflux, which may be present in the oral fluids. 11 CocaCola, which presents phosphoric acid and other pigments and substances in its composition; and red wine, due to the low pH and to promote high color change in the restorative materials. 12 The mechanical challenge was performed by toothbrushing, which could influence the surface degradation of restorative materials.…”
Section: Discussionmentioning
confidence: 99%
“…1 This study employed chemical challenges with acidic solutions, such as hydrochloric acid to simulate the gastric reflux, which may be present in the oral fluids. 11 CocaCola, which presents phosphoric acid and other pigments and substances in its composition; and red wine, due to the low pH and to promote high color change in the restorative materials. 12 The mechanical challenge was performed by toothbrushing, which could influence the surface degradation of restorative materials.…”
Section: Discussionmentioning
confidence: 99%
“…Also factors like the cross-link nature of the resin matrix, and the solvent sorption uptake have a direct effect on composite resins degradation [20]. Previous studies showed that the increase of composite resins roughness in acidic solutions is probably due to their soften surface that leaches the resin components and displaces the filler particles [21][22][23].…”
Section: Discutionsmentioning
confidence: 99%
“…For continuous cola immersion, each specimen was immersed in 10 mL of cola drink (Coca Cola ® , SP, Brazil -pH 2.3) at room temperature in individual containers for 5 weeks [10]. Samples of control 2 group were immersed in 10 mL of artificial saliva for 5 weeks.…”
Section: Erosive Challenge and Continuous Cola Immersionmentioning
confidence: 99%
“…Many studies have been conducted to evaluate the surface properties of restorative materials after erosive challenge [8][9][10], but little information is available in literature about the surface properties of composites for bonding orthodontic brackets to enamel after erosion [6].…”
Section: Introductionmentioning
confidence: 99%